Microwave-Assisted Synthesis of Anti-Microbial Chromones - Mai, Nguyen Thi Thanh; Ha, Nguyen Manh (VNU Journal of Science: Natural Sciences and Technology; Vol 39 No 4DO - 10.25073/2588-1140/vnunst.5413, 2023)
Ten new chromone derivatives were synthesized from the original 2-4-6-trihydroxyacetophenone using microwave irradiation. The product's structures were confirmed by FT-IR, 1 H-NMR, and 13 C-NMR spectra data. The anti-microbial activities of the obtained compounds were tested by the disc diffusion method. The results showed that most chromones have significant biological activities against Candida albicans .